PENGARUH RASIO PROFITABILITAS TERHDAP KINERJA KEUANGAN DI PT ADHI KARYA (PERSERO) TBK - Telaumbanua, Novia Intan Berlian (Jurnal Ilmiah Mahasiswa Nias Selatan, 2025)
The author is interested in knowing the effect of profitability ratios on financial performance at PT Adhi Karya (Persero) Tbk. The type of research used is quantitative research that is causal in nature (cause and effect). The data analysis used is multiple linear regression analysis. The results of this research show that profitability: GPM, NPM, OPM, ROA AND ROE have a significant influence on financial performance. Furthermore, in this research, the multiple linear regression analysis equation was obtained, namely: Y = 185,838 + -8,805(X1)+-2,337(X2)+-1,788(X3)+-76,649(X4)+14,932(X5). This means that the constant value is 185,838. This shows that if the variable means that if the x value is 0 then the financial performance value is 185,838. GPM regression coefficient of -8.805; This means that if GPM is increased by 1%, there will be a decrease in the financial performance variable of -8,805 assuming other independent variables are constant. With this negative influence, it means that GPM and financial performance show an opposite relationship. If the variable increases, the gross profit margin and financial performance will decrease, and vice versa, the NPM coefficient is -2,337; This means that if NPM is increased by 1%, there will be a decrease in financial performance variables of -2,337 assuming other independent variables are constant. With this negative influence, it means that net profit margin and financial performance show an opposite relationship. If the variable increases, the net profit margin and financial performance will decrease, and vice versa, the OPM coefficient is -1,788; This means that if the OPM is increased by 1%, there will be a decrease in the financial performance variable of -1,788, assuming the other independent variables are constant. With this negative influence, it means that operational profit margin and financial performance show an opposite relationship. If the variable increases, the operational profit margin and financial performance will decrease, and vice versa, the ROA coefficient is -76,649; This means that if ROA is increased by 1%, there will be a decrease in the financial performance variable by -76,649 assuming other independent variables are constant. With this negative influence, it means that return on assets and financial performance show an opposite relationship. If the variable increases, return on assets and financial performance will decrease, and vice versa, the ROE coefficient is 14,932; This means that if ROE is increased by 1%, there will be a decrease in the financial performance variable (Y) by 14,932. assuming other independent variables are constant.